Analisis Gaya Hidup Hedonis, Harga, dan Kualitas Produk serta Pengaruhnya terhadap Keputusan Pembelian Sepeda di Era Pandemi Covid-19 - Rama Prasetiyo, Aji; Andjarwati, Anik Lestari (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The Pandemic Covid-19 makes many people have to live their lives by starting new habits. The form of activity to maintain the health of the body is to exercise. Cycling is one of the trending sports that people love during the Covid-19 pandemic. It was noted that there was a demand for the domestic bicycle market. Bicycle manufacturers are experiencing intense competition. They compete to provide bicycles of good quality at competitive prices. The existence of this tren raises the community's hedonic lifestyle, such as shopping activities and hunting bicycles for fun. The purpose of this research to analyze the effect of hedonic lifestyle, price, and product quality on United's bicycle purchase decisions in Tulungagung Regency. This study uses a sample of 220 respondents who live in Tulungagung Regency with male and female genders of at least 16 years. The sampling method was judgmental sampling with a Likert scale as a measuring instrument. The analysis in this research uses multiple linear regression equation models with SPSS 26. The results showed that the variables of hedonic lifestyle, price, and product quality significantly and positively influenced purchase decisions. As a suggestion, United can increase sales by offering affordable prices and still provide the best quality.